The Establishment of Core Competencies for Canadian Genetic Counsellors: Validation of Practice Based Competencies. Issue 6 (14th September 2013) - Ferrier, Raechel Ann; Connolly‐Wilson, Mary; Fitzpatrick, Jennifer; Grewal, Sonya; Robb, Laura; Rutberg, Julie; Lilley, Margaret; ,
Abstract: Numerous groups of health professionals have undertaken the task of defining core competencies for their profession. The goal of establishing core competencies is to have a defined standard for such professional needs as practice guidelines, training curricula, certification, continuing competency and re‐entry to practice. In 2006, the Canadian Association of Genetic Counsellors (CAGC) recognized the need for uniform practice standards for the profession in Canada, given the rapid progress of genetic knowledge and technologies, the expanding practice of genetic counsellors and the increasing demand for services. We report here the process by which the CAGC Practice Based Competencies were developed and then validated via two survey cycles, the first within the CAGC membership, and the second with feedback from external stakeholders. These competencies were formally approved in 2012 and describe the integrated skills, attitudes and judgment that genetic counsellors in Canada require in order to perform the services and duties that fall within the practice of the profession responsibly, safely, effectively and ethically.